2017
DOI: 10.1111/ecoj.12451
|View full text |Cite
|
Sign up to set email alerts
|

Wet Laws, Drinking Establishments and Violent Crime

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 97 publications
1
20
0
Order By: Relevance
“…A large body of empirical research looks at the effect of alcohol consumption (but not necessarily HED) on a wide range of outcomes. The existing evidence suggests that as alcohol consumption increases so do motor vehicle accidents and alcohol related deaths (Chaloupka, Saffer, and Grossman 1993;Ruhm 1996;Dee 1999;Dobkin 2009, 2011), fatal and nonfatal injuries and A&E admissions (Levitt and Porter 2001;Adams, Blackburn, and Cotti 2012;Marcus and Siedler 2015;Carpenter and Dobkin 2017;Hansen 2015), arrests and crime (Biderman, De Mello, and Schneider 2010;Heaton 2012;Carpenter and Dobkin 2015;Anderson, Crost, and Rees 2016), teen childbearing and abortions (Dee 2001), child abuse (Markowitz and Grossman 2000), and work days lost due to industrial injuries (Ohsfeldt and Morrisey 1997), while educational attainment goes down (Carrell, Hoekstra, and West 2011) as well as employment (Terza 2002). 3 Whether such effects are driven by alcohol consumption in general or HED in particular remains to be seen.…”
Section: Accepted Articlementioning
confidence: 99%
“…A large body of empirical research looks at the effect of alcohol consumption (but not necessarily HED) on a wide range of outcomes. The existing evidence suggests that as alcohol consumption increases so do motor vehicle accidents and alcohol related deaths (Chaloupka, Saffer, and Grossman 1993;Ruhm 1996;Dee 1999;Dobkin 2009, 2011), fatal and nonfatal injuries and A&E admissions (Levitt and Porter 2001;Adams, Blackburn, and Cotti 2012;Marcus and Siedler 2015;Carpenter and Dobkin 2017;Hansen 2015), arrests and crime (Biderman, De Mello, and Schneider 2010;Heaton 2012;Carpenter and Dobkin 2015;Anderson, Crost, and Rees 2016), teen childbearing and abortions (Dee 2001), child abuse (Markowitz and Grossman 2000), and work days lost due to industrial injuries (Ohsfeldt and Morrisey 1997), while educational attainment goes down (Carrell, Hoekstra, and West 2011) as well as employment (Terza 2002). 3 Whether such effects are driven by alcohol consumption in general or HED in particular remains to be seen.…”
Section: Accepted Articlementioning
confidence: 99%
“…2 Several quasi-experimental studies have documented effects of alcohol policies on crime, using variation driven by the minimum legal drinking age (Carpenter and Dobkin, 2015), taxes (Cook and Moore, 1993b;Markowitz and Grossman, 2000;Markowitz, 2005;Durrance et al, 2011;Cook and Durrance, 2013), drunk driving laws (Carpenter 2005(Carpenter , 2007, and changes in "wet" laws (Biderman, De Mello, and Schneider, 2010;Anderson, Crost, and Rees, 2014). Of those studies that include estimated effects on sexual assault or rape, Cook and Durrance (2013) and Markowitz (2005) found no statistically significant evidence that beer taxes affect the probability of rape, Cook and Moore (1993b) found that beer tax increases reduce rape rates, Anderson et al (2015) found that the number of licensed premises has a positive effect on rape rates, and Carpenter and Dobkin (2015) find no evidence of a discontinuity in arrest rates for rape at the minimum legal drinking age.…”
Section: Introductionmentioning
confidence: 99%
“…Given the public health and security risks associated with excessive alcohol consumption, governments have often struggled to design and implement effective public policies. Governments have levied higher taxes on alcohol, raised the drinking age, imposed curfews on establishments serving alcohol, cracked down on public consumption (so-called "open container" laws), have provided fewer liquor licences to alcohol-serving establishments (and more generally limited alcohol availability), and conducted informational campaigns to expose the dangers of (over)consumption and encourage the responsible use of alcohol (Pridemore and Snowden, 2009;Lovenheim and Steefel, 2011;Heaton, 2012;Grönqvist and Niknami, 2014;Marcus and Siedler, 2015;Anderson et al, 2016). The literature has concluded that restricting alcohol availability tends to reduce interpersonal violence and the commission of crimes, but reported effects are small.…”
Section: Motivationmentioning
confidence: 99%